Natural gas regeneration of carbonate melts following SO2 capture from non-ferrous smelter emissions. Issue 35 (18th April 2017) - Dosmukhamedov, Nurlan; Kaplan, Valery; Zholdasbay, Yerzhan; Wachtel, Ellen; Lubomirsky, Igor
Abstract : Sulfur emission in the form of SO2 in flue gases is the one of the most serious atmospheric pollutants associated with coal combustion and non-ferrous metal production. Abstract : Sulfur emission in the form of SO2 in flue gases is the one of the most serious atmospheric pollutants associated with coal combustion and non-ferrous metal production. The carbonate eutectic method for removing SO2 from flue gases at 723–923 K was initially proposed in the 1970's but despite its great efficiency (SO2 concentration in the flue gas after purification reached 0.003 vol%) it could not be implemented by industry due to the complexity of the carbonate melt regeneration stage. Earlier we proposed a method suited to coal-firing power stations where the melt was regenerated using CO as a reducing agent. However, most metallurgical plants do not use coal and therefore lack a large source of CO. Here we propose a method for removing sulfur from the carbonate eutectic melt by purging it with natural gas or a natural gas/air mixture, which are available in the vast majority of metallurgical plants. This reaction leads to the reduction of sulfate to H2 S gas that leaves the melt. The experiments we conducted show that nearly complete sulfur removal from the melt is possible at 823 K and that the reaction rate is sufficiently high for a large scale process. The proposed modifications provide solutions to two major problems previously encountered: (i) high temperature corrosion of the reaction cell can be avoided, since a stainless steel cell with high chromium content is stable with respect to the carbonate eutectic melt at 823 K, and (ii) removal of sulfur in the form of H2 S provides considerable freedom in choosing the final industrially useful product: either sulfuric acid, using H2 S dry combustion, or elemental sulfur via the Claus process. One can foresee that this carbonate melt-based SO2 removal technique may become a practical and economically attractive method for limiting sulfur emission to the atmosphere from non-ferrous metallurgical processing plants.